2007
DOI: 10.1111/j.1365-2850.2007.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing services for the carers of young adults with early‐onset psychosis – implementing evidence‐based practice on psycho‐educational family intervention

Abstract: This paper describes a series of practice and service development initiatives to incorporate the family-inclusive approach into the newly established Early Intervention in Psychosis Service in Berkshire, England. Following a local study on carers' experiences and needs from those who cared for a young adult with a first-episode psychosis (FEP), a series of flexible services for this group of carers has been developed incorporating the much-researched psycho-educational family interventions. The findings of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…This can be channeled into political action through participation in family groups, such as the National Alliance on Mental Illness, which has played a strong role in obtaining legal parity of coverage for health care. As described in other studies (18,19), this study showed that families want information and support and more involvement in the care and recovery of their loved ones. Their wishes are consonant with calls by the President’s Commission for more patient- and family-centered care (29) and calls by the IOM for involving patients and families in the design, administration, and delivery of treatment and recovery services (31).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This can be channeled into political action through participation in family groups, such as the National Alliance on Mental Illness, which has played a strong role in obtaining legal parity of coverage for health care. As described in other studies (18,19), this study showed that families want information and support and more involvement in the care and recovery of their loved ones. Their wishes are consonant with calls by the President’s Commission for more patient- and family-centered care (29) and calls by the IOM for involving patients and families in the design, administration, and delivery of treatment and recovery services (31).…”
Section: Discussionsupporting
confidence: 81%
“…Focus groups have identified that families want more involvement, support, advice on managing symptoms, aid in navigating treatment systems, and contact with other families (18,19). Specifically, families requested multifamily psychoeducational groups in which patients are not present, rapid outreach after diagnosis, phone support from trained peers, and information on illness and treatment.…”
mentioning
confidence: 99%
“…FEP carers tend to be unfamiliar with symptoms and behaviors associated with psychosis, unfamiliar with medications and side-effects, unfamiliar with mental health services and systems, with limited knowledge of the process of recovery or common treatments, and inexperienced in developing coping mechanisms (Lowenstein, et al, 2010;Sin, Moone, & Newell, 2007). Since onset of FEP is typically early 20s, individuals remain living with their families for an extended period, resulting in the parental role being extended for carers (Askey et al, 2007;Lowenstein et al, 2010).…”
Section: Needs Of First Episode Psychosis Carersmentioning
confidence: 98%
“…Several papers described embedding support within service or treatment (e.g. Gopalan, et al, 2014;Lee et al, 2009;Sin, Moone & Newell, 2007). Sometimes support aimed to empower the consumer or family, for example, the clinician supported parents to solve their own problems, rather than rely on professionals (Lee et al, 2009).…”
Section: Instrumental Emotional and Social Supportmentioning
confidence: 99%
“…Research on "age" as a variable in FFP needs further evidence: for example, day hospital treatment for infants, toddlers and preschoolers (Furniss et al, 2013); and "early" onset diagnoses such as psychosis (Sin et al, 2007) and bipolar disorder (Miklowitz et al, 2006) where families may be encountering mental health clinicians and services for the first time, and when the consumer is a child, youth or transitioning adult. Other areas include family psychoeducational needs in relation to the differences between developmental-and illness- Further research is required to explore whether particular practice settings and professional disciplines should dictate the range of family-focused activities that occur, especially considering the continuum of family-focused practices that exist and the potential differences in the capacity of different healthcare disciplines to engage in FFP (see Maybery et al, 2014).…”
Section: Practices Of Ffpmentioning
confidence: 99%